East Africa after liberation conflict, security and the state since the 1980s - Fisher, Jonathan 1985- (Cambridge University Press, 2022)
"Between 1986 and 1994, East Africa's postcolonial, political settlement was profoundly challenged as four revolutionary 'liberation' movements seized power in Eritrea, Ethiopia, Rwanda and Uganda. After years of armed struggle against vicious dictatorships, these movements transformed from rebels to rulers, promising to deliver 'fundamental change'. This study exposes, examines and underlines the acute challenges each has faced in doing so. Drawing on over 130 interviews with the region's post-liberation elite, undertaken over the course of a decade, Jonathan Fisher takes a fresh and empirically-grounded approach to explaining the fast-moving politics of the region over the last three decades, focusing on the role and influence of its guerrilla governments. East Africa after Liberation sheds critical light on the competing pressures that post-liberation governments contend with as they balance reformist aspirations with accommodation of countervailing interests, historical trajectories and their own violent organisational cultures."--
Literaturverzeichnis Seite 288-311, Register
Keywords: Geschichte 1986-2020; National liberation movements -- Africa, Eastern; Security, International -- Africa, Eastern; Revolution; Diktatur; Regierungswechsel; Revolutionäre Bewegung; Africa, Eastern -- Politics and government -- 1960-; Eritrea; Äthiopien; Uganda; Ruanda; Ostafrika / Regionale internationale Prozesse und Tendenzen / Unabhängigkeitsbewegung/Befreiungsbewegung / Nationale Befreiung / Guerillaverbände / Regierungswechsel/Machtwechsel / Innenpolitischer Konflikt / Aufstand/Revolte / Politischer Wandel / Politische Führung (Gruppe); East Africa / Regional international processes and tendencies / Independence movements/liberation movements / National liberation / Guerilla units / Changes of government / Domestic political conflicts / Uprisings/revolts / Political change / Political leaders; Eritrea / Äthiopien / Ruanda / Uganda; Eritrea / Ethiopia / Rwanda / Uganda; Africa, Eastern / Politics and government / 1960-